Save it for Later: memories of a Lambe-Lambe Theater process with objects that evoke memories (Móin-Móin Magazine - Studies in the Art of Puppetry, 2024)
This article records the memories of a Lambe-Lambe Theater assembly process with objects that evoke memories. This record in words follows a trajectory that begins with the DESIRE to build a show and the IDEAS that open countless paths, consequently passing through the NEED to choose the most viable paths until the actual REALIZATION of the itinerary. During the course of the text, the ENCOUNTERS, REENCOUNTERS, DISCOVERIES and REDISCOVERIES are highlighted that underlie the creative process of the scene and become part of these memories that permeate objects and people.
Keywords: object theater; Lambe-Lambe theater; evocative objects; memories